Product market advertising, heterogeneous beliefs, and the long-run performance of initial public offerings - Chemmanur, Thomas; Yan, An (Journal of Corporate Finance, 2017)
We study the long-run effects of product market advertising on the equity of firms conducting initial public offerings (IPOs). We find that firms going public with a greater extent of advertising prior to their IPOs are valued higher both in the IPO as well as in the immediate aftermarket, are associated with greater upward price revisions from the pre-IPO filing range means, and have smaller long-run post-IPO stock returns. The above results hold even after controlling for the effects of investor attention, as proxied by the pre-IPO media coverage received by firms going public. We show, using a number of additional tests, that the above findings are consistent with the implications of the heterogeneous beliefs theories of Miller (1977), Harrison and Kreps (1978), and Morris (1996), along with an assumption that product market advertising increases the heterogeneity in outside investor beliefs about firms going public.